Seasonal changes in habitat use and behavior of the threatened Pampas meadowlark Leistes defilippii - Álvarez, Agustín Gabriel; Cozzani, Natalia Carolina; Zalba, Sergio Martín; Tizon, Francisco Rodrigo (Sage Publications, 2024)
The Pampas grasslands’ biodiversity is severely threatened by habitat modification, as is the case for the Pampas meadowlark (Leistes defilippii). Here we study the areas used by the species throughout the year in the Southern Pampas of Argentina, in association with seasonal changes in behavior, in an attempt to provide information for its effective conservation. We selected four grassland sites with livestock activities in which we studied vegetation characteristics and the abundance and behavior of the Pampas meadowlark, during breeding and non-breeding seasons. The species was absent in sites with higher bare ground cover and lower cover of >30 cm vegetation, and with high proportions of forb, shrub or exotic grass species. In those areas where the Pampas meadowlark was present during the breeding season, its abundance was higher where the grassland was entirely dominated by native grasses, and abandoned another site when the grassland became dominated by introduced plant species, after the breeding period. We are the first to report the behavior of a Pampas meadowlark population throughout an entire year with its seasonal changes. Our results and description of the behavior throughout the year highlight the importance of structural heterogeneity of the grasslands, determined by a low intensity of grazing, for the breeding of the Pampas meadowlark. Also, features associated with breeding habitat can’t predict the presence of flocks during the non-breeding season, as noted in our results for vegetation structure, but vegetation composition, food availability and landscape variables could play an important role in determining which areas serve as appropriate habitat during the non-breeding season, when large flocks search the grasslands for food. A better understanding of the habitat requirements and the use of space at different scales by the Pampas meadowlark will allow the identification of the most urgent and effective measures for its conservation.